Investigate accounting practices by binte biluhuta sellers - Mohamad Anwar Thalib; Vindi Paputungan; Widy Pratiwi Monantun; Ulvarien Ismail; Fatmawaty Damiti; Faisal Abdullah (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - This study aims to investigate simple accounting practices focusing on earning income by binte biluhuta sellers based on the local wisdom values of the Gorontalo people.Method - This study uses an Islamic paradigm with an Islamic ethnomethodology approach. Futher, the study uses the qualitative approach through observation and interview, In addition, there are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy.Result - The results of the study showed that sellers earned higher income during the holy month of Ramadan most of the time except pandemic (covid-19) and rainy season. Accounting for this income is conditional on the value of patience (sabari) and gratitude (mosukuru) to obtain blessed sustenance from Allah (The Almighty God).Implication - The results of this study presented the concept of income accounting by binte biluhuta sellers with local wisdom and Islamic religiosity values.Originality - This accounting study is the first to raise accounting practices by binte biluhuta sellers that are conditional on the local cultural and religious values of the Gorontalo people.